Investigations in massive 3D gravity - Accioly, Antonio Jose [UNESP]; Helayel-Neto, Jose; Morais, Jefferson; Scatena, Eslley [UNESP]; Turcati, Rodrigo (Amer Physical Soc, 2011)
Some interesting gravitational properties of the Bergshoeff-Hohm-Townsend model (massive 3D gravity), such as the presence of a short-range gravitational force in the nonrelativistic limit and the existence of an impact-parameter-dependent gravitational deflection angle, are studied. Interestingly enough, these phenomena have no counterpart in the usual Einstein 3D gravity. In order to better understand the two aforementioned gravitational properties, they are also analyzed in the framework of 3D higher-derivative gravity with the Einstein-Hilbert term with the wrong sign.